Influence of Parent Material and Topography on Water Stable Aggregates in Chotanagpur Soils - Ratnakar, R.P.; Sahi, B.P.; Sinha, B.P. (Journal of Soil and Water Conservation, 2022)
It has been shown that aggregate formation in soils depends upon the presence of small primary particles that may be aggregated, the coagulation or flocculation of the particles and the cementation of the coagulated materials into stable aggregates. Hence, formation of aggregates is the outcome of physical, chemical and biological reactions.